SEJARAH KEBANGKITAN MADRASAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM - Islamiyah, Nurul (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This article discusses the history of the rise of madrasas as Islamic educational institutions. Regarding the emergence of the madrasa, various historical accounts credit its sensitivity to Nizham al-Mulk. However, there are also those who state that madrasas have existed since the 4th century H and are associated with the residents of Naisabur. According to Makdisi, the separation of Islamic education institutions from mosques to madrasas occurred indirectly but through a transitional stage, namely the Khan mosque. Several theories emerged regarding the process of transformation from a mosque to a madrasa. Ahmad Syalabi explained, unlike Maqdisi, the mosque was transformed directly into a madrasa. It is hoped that this paper will be able to describe the increase in Islamic educational institutions, starting from the mosque, as a place of love, to turning it into a madrasah, as an agent of formal Islamic education organizations.